Analysis of Various Learning Styles of STKIP PGRI Sidoarjo Students - Abdil Aziz, Muhammad Faris; Andjariani, Endang Wahju (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This study aims to (1) describe the relationship between the learning styles of PGRI College students and language skills, (2) find out solutions to the problem of the diversity of learning styles of PGRI College students. The type of research used is a literature study. Sources of data in this study using secondary data sources. The data analysis technique of this research uses Miles and Huberman data analysis. According to Miles and Huberman (In Sugiyono, 2014: 247) suggest that the activities in data analysis are carried out interactively and take place continuously until complete, so that the data is saturated. Activities in data analysis are data reduction, data display and conclusion drawing/verification data. The results of the analysis state (1) that to find out the relationship between the learning styles of PGRI Higher Education students who are more prominent towards language skills is the Auditory Learning Style. Because the Auditory learning style has a stronger relationship to students' listening skills and English language skills, (2) to be able to find solutions to overcome various problems of student learning styles that tend to have certain learning styles such as visual, auditory and kinesthetic learning styles.